Collecte et gestion des débris post-cycloniques à Saint-Martin (Antilles françaises) après le passage du cyclone Irma (sept. 2017) - Freddy Vinet; Mathieu Peroche; Philippe Palany; Frédéric Leone; Monique Gherardi; Delphine Grancher; Annabelle Moatty; Stéphanie Defossez (Cybergeo, 2020)
In the aftermath of a disaster, the debris caused by the destruction of property or vegetation become a crucial problem. The increase in the volume of debris, the growing requirements for environmental protection, the cost of waste collection and treatment for local authorities or companies are increasingly complex challenges for lands subject to natural, technological or political disasters (conflicts). The landfall of the cat 5 hurricane Irma and, to a lesser extent Jose, generated an amount of debris estimated up to 60 000 metric tons only for the French part of the island of St. Martin, i.e. 1.7 metric ton per capita. The waste collection and treatment represented a huge challenge. The waste collection took four months whereas the full process (treatment and recycling) was still going on in November 2018. Operations have been hampered by the cyclone itself (destruction of infrastructure and material resources, lack of laborers…) and by the constraints of insularity (low volume to value, lack of storage areas...). On the other hand, Saint-Martin benefits from a single public operator (the collectivity of Saint-Martin) and a recycling and landfill site called “Écosite” with rising skills in waste valorization despite modest funds. The example of Saint-Martin shows all the difficulties of post-cyclonic debris management and emphasizes the dependence of the production of debris and their treatment to the characteristics of the island.